2020
DOI: 10.3390/e22101126
|View full text |Cite
|
Sign up to set email alerts
|

Low- and High-Drag Intermittencies in Turbulent Channel Flows

Abstract: Recent direct numerical simulations (DNS) and experiments in turbulent channel flow have found intermittent low- and high-drag events in Newtonian fluid flows, at Reτ=uτh/ν between 70 and 100, where uτ, h and ν are the friction velocity, channel half-height and kinematic viscosity, respectively. These intervals of low-drag and high-drag have been termed “hibernating” and “hyperactive”, respectively, and in this paper, a further investigation of these intermittent events is conducted using experimental and nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Indeed, the hibernating intervals are approaches to lower-branch TW solutions, while the active intervals are close to an upper-branch TW solution. Very recently, this low-and high-drag intermittency is observed and quantified in experiments and in good agreement with DNS results [40]. It is worth noting that the temporal and spatial analyses on the relationship between temporal dynamics in minimal domains and spatiotemporal dynamics in extended domains also yield very similar results for the hibernating and active intervals [41] at friction Reynolds numbers ranging from 70 to 100.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, the hibernating intervals are approaches to lower-branch TW solutions, while the active intervals are close to an upper-branch TW solution. Very recently, this low-and high-drag intermittency is observed and quantified in experiments and in good agreement with DNS results [40]. It is worth noting that the temporal and spatial analyses on the relationship between temporal dynamics in minimal domains and spatiotemporal dynamics in extended domains also yield very similar results for the hibernating and active intervals [41] at friction Reynolds numbers ranging from 70 to 100.…”
Section: Introductionsupporting
confidence: 81%
“…In particular. a grid convergence and domain dependence have been tested in our previous studies for no-control cases [41,40] and in the current study for control cases. A numerical grid system is generated on N x × N y × N z (in x, y, and z) meshes, where a Fourier-Chebyshev-Fourier spectral spatial discretization is applied to all variables.…”
Section: Problem Formulationmentioning
confidence: 99%
“…( a ) Spanwise distributions of the time averaged velocity in the midplane , and ( b ) the time averaged velocity profiles at different spanwise positions. The measurements of Reference [ 33 ] are added in ( b ) as references.…”
Section: Figurementioning
confidence: 99%
“…Turbulence intensities at the channel center are measured and are found to increase rapidly around Re = 1050, reach a peak at Re = 1140, and then gradually decrease with increasing Re [ 29 ]. The intermittent low- and high-drag events are investigated numerically and experimentally [ 30 , 31 , 32 ], and it is found that the conditionally averaged Reynolds shear stress is higher than the mean value during the low-drag events [ 33 ]. Based on simulations of channel flows with constant pressure gradients, a linear correlation for the wall shear stress is observed between its kurtosis and its skewness squared [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embedded in a turbulent flow is inherent intermittency. The dynamics of wallbounded turbulence fluctuate between high, intermediate, and low-drag states in a stochastic fashion, which illuminates the self-sustaining process in shear flows [1][2][3][4]. The most straightforward simulation approach to identify the intermittency and self-sustaining structures is the so-called minimal flow unit (MFU) approach [5].…”
Section: Introductionmentioning
confidence: 99%